NHC-stabilized silyl-substituted silyliumylidene ions. Issue 28 (26th June 2019) - Frisch, Philipp; Inoue, Shigeyoshi
Abstract : Expanding the scope of N-heterocyclic carbene stabilized silyliumylidene ions: isolation of the first silyl-substituted Si(ii ) cations. Abstract : The first silyl-substituted silyliumylidene ions are reported. The scope of a previously described convenient one-step procedure for the preparation of N-heterocyclic carbene (NHC) stabilized silyliumylidene ions via dehydrochlorination from a Si(iv ) precursor with NHCs is expanded to silyl-based substituents as well as aryl substituents with reduced steric bulk.